Nigerian Politics, Economic Development, and the Role of Human Rights Organisations on Elections - Obasi, Nwele James; Akwawa, Uduimoh Anthony (International Journal of Sustainable Development & World Policy, 2015)
This paper examines the nexus between governments, human right organisations and electorates on elections in relation to economic development through human capacity building templates of society. The society problems, the complexities of business cycle and development that we face today, is leadership inability to handle democratic indices and draw a line between marginal utility and social value. The conflict line services of affluence that is measured on regressional competition is grossly taking over the political field and true democracy becoming unattainable feat in most economies of the world, and particularly in Nigeria. This finding reveals that most politicians think it is not necessary to learn the specific bases of power as they are meant to provide a sense of the variety and complexity of power, and not as an exhaustive list of its important sources. In developing countries it is of essence to make all political template in the field of play favourable to even development, so that, positive government actions permeate all channels in the process. This research examines the broad principles of all about politics especially, about the politics of democracies, like the United States, Britain, the State of Israel, and Italy, et cetera. The relationship between the Nigerian government, human right organisations, the electorate and social security and peace needs to be harmonised for secured tranquillity in our society. The findings of this study reveal that politics and economic development, elections, democracy, electorates and human right organisations has a nexus that cannot be overemphasised. This is because the growth of economy is dependent on how the indices of these compound templates are harmonised. According to Shively (2001), “Despite the complexity and elusiveness of power, we can say that all politics is based on some form of power and that its sources may be highly varied. For most practical applications of politics, however, it is not necessary to specify in detail exactly what sort of power is involved.